القضاء على الغالب فى الإختلاس : دراسة مقارنة بين الفقه الإسلامي وقانون إندونيسيا أنموذجا - حميدي، مختم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study tries to elaborate the understanding of trial in absentia according to Islamic criminal law and Indonesian criminal law, as well as the procedure in which a trial is conducted by making comparison between the two. For the study, three approaches have been adopted. The first is the inductive method which traces the texts which are written in the Holy Quran and Sunnah as well as the views of scholars on trial in absentia and matters related thereto, the second is the analytical approach which reviews the topic in the books of past scholars and analyses on criminal matters related by collecting the data on this subject in the works of traditional and modern scholars, and the last approach is the comparative method which compares the opinions of scholars in Islamic and Indonesian criminal law, choosing which statement is to prevail. It is concluded that Islamic and Indonesian criminal laws have strictly prohibited the act of corruption as it is a crime that relates to money and is considered in criminal law as extra ordinary crime. Both laws allow trial in absentia in this matter. The trial in absentia is not much different than the trial in the presence of the parties concerned, provided adequate opportunity to defend the rights is given to achieve justice if the defendant appears in the court before or after the judge gives the sentence. The subject of trial in absentia in Islamic criminal law is long and complex as the scholars have many views and arguments. The discussion in criminal law is extensive, but in summary it does not include all the necessary measures, therefore it needs to be reviewed and clarified with the help of Islamic jurisprudence.